Turning Platelets Off and On: Role of RhoGAPs and RhoGEFs in Platelet Activity - Comer, Shane P. (Frontiers in Cardiovascular Medicine, 2022)
Platelet cytoskeletal reorganisation is a critical component of platelet activation and thrombus formation in haemostasis. The Rho GTPases RhoA, Rac1 and Cdc42 are the primary drivers in the dynamic reorganisation process, leading to the development of filopodia and lamellipodia which dramatically increase platelet surface area upon activation. Rho GTPases cycle between their active (GTP-bound) and inactive (GDP-bound) states through tightly regulated processes, central to which are the guanine nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs). GEFs catalyse the dissociation of GDP by inducing changes in the nucleotide binding site, facilitating GTP binding and activating Rho GTPases. By contrast, while all GTPases possess intrinsic hydrolysing activity, this reaction is extremely slow. Therefore, GAPs catalyse the hydrolysis of GTP to GDP, reverting Rho GTPases to their inactive state. Our current knowledge of these proteins is constantly being updated but there is considerably less known about the functionality of Rho GTPase specific GAPs and GEFs in platelets. In the present review, we discuss GAP and GEF proteins for Rho GTPases identified in platelets, their regulation, biological function and present a case for their further study in platelets.